The Inauthenticity of the Main Characters as an Impact of Totalitarian System Seen in George Orwell’s 1984 - Renaldi, Adi; Widyastuti, Dewi (Journal of Language and Literature, 2015)
1984 is a dystopian novel by George Orwell that clearly describes the life under totalitarian government. Totalitarianism is not merely a political system but also movement that goes beyond private, public, and political sphere. Totalitarian government dreams of uniformity in all aspects of life and they pursue for global domination. In order to reach for global domination and their ideal version of state, totalitarian government does not allow freedom in all aspects of life. The pursuit of global domination requires some strategies to make the society in uniformity. The strategies applied are propaganda, terror, and indoctrination. These strategies make the main characters lose the freedom and become alienated from the self and the society. Alienation and the lost of freedom also lead to inauthenticity, since they are related to each other. Inauthenticity can be caused by repression from external agents in which a person cannot do anything spontaneously since he is being dictated by other people and he cannot express what they feel freely.Keywords: totalitarianism, inauthenticity, alienation